Proposed Improvements to Reduce the Risk Work Accidents on CV HB with FMEA and HAZOP Method - Julian Sugianto, Martin; Alexander Reggy, Revaldo; Aulia Fadhilah, Hana; Benedict, Dustin; Sukapto, Paulus (Ann Publisher, 2024)
A company called CV HB makes socks based on what its customers want. Bandung is home to CV HB. Several machines, including Santoni, Dakong, Obrass, Stock Steam, and others, are employed in CV HB's sock production process. Numerous personnel who are in charge of running the machinery and performing other production tasks are also a part of the production process. The execution of health and safety protocols has yet to be well-executed in the production sector. The organization saw 24 workplace accidents between 2019 and 2023, including injuries from needles and blades, hands stuck in machinery, brain injuries from machines, slipping down stairs, and many more incidents. In order to address health and safety concerns at CV HB, the research attempts to pinpoint the root causes of workplace mishaps and offer suggestions for enhancement. Hazard and Operability Review (HAZOP) and Failure Mode and Effects Analysis (FMEA) were the methodologies used in the investigation. A few suggestions for improvement for the chosen departments are using material handling tools during the material retrieval process, posting warnings about machines with sharp parts, requiring protective gear like masks and gloves, designing foam padding for sharp machine parts, and installing fans.